2015
DOI: 10.1111/1365-2745.12482
|View full text |Cite
|
Sign up to set email alerts
|

Frost sensitivity of leaves and flowers of subalpine plants is related to tissue type and phenology

Abstract: Summary Harsh abiotic conditions – such as low temperatures that lead to spring and summer frost events in high‐elevation and high‐latitude ecosystems – can have strong negative consequences for plant growth, survival and reproduction. Despite the predicted increase in episodic frost events under continued climate change in some ecosystems, our general understanding of the factors associated with frost sensitivity of reproductive and vegetative plant structures in natural plant communities is limited. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…Thus, although we detected frost damage, the frost events might not have been severe enough to affect flower production. Finally, we did not find any significant frost damage to Delphinium or Potentilla, which is not surprising given that Delphinium is highly frost tolerant (CaraDonna & Bain, ), and Potentilla bloomed after the date of last frost, even in the snow removal treatment. Several studies have documented a direct link between frost and flower production for mid‐ to late‐blooming species (Augspurger, ; Inouye, ; Pardee et al, ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, although we detected frost damage, the frost events might not have been severe enough to affect flower production. Finally, we did not find any significant frost damage to Delphinium or Potentilla, which is not surprising given that Delphinium is highly frost tolerant (CaraDonna & Bain, ), and Potentilla bloomed after the date of last frost, even in the snow removal treatment. Several studies have documented a direct link between frost and flower production for mid‐ to late‐blooming species (Augspurger, ; Inouye, ; Pardee et al, ).…”
Section: Discussionsupporting
confidence: 64%
“…However, frost damage did not translate into lower flower production for either species. One reason may be that the night‐time temperatures during the natural frost events in our study were usually between −1 and −4 ° C, and early blooming species have been shown to be able to withstand these mild frost events (CaraDonna & Bain, ). However, Gezon et al () did find that frost negatively impacted Claytonia seed set in 2012, a year where the snow melted out particularly early and temperatures reached −8 ° C once plants had emerged.…”
Section: Discussionmentioning
confidence: 94%
“…; Vitasse et al . ; CaraDonna & Bain ), leading to the same risk of freezing damage among species (Lenz et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Hereafter, we refer to each species by genus. We chose three mid‐summer flowering species because they likely preform their buds (Inouye, Morales, & Dodge, ), and their leaves and other tissues have been shown to be more frost sensitive than their earlier season congeners (CaraDonna & Bain, ); thus, their floral and flowering traits may be susceptible to early season frost damage. Erigeron produces light pink‐to‐purple, hermaphroditic flowers, with 1–11 flower heads per stem (Robertson, ), and on average 15 stems per plant (G.L.…”
Section: Methodsmentioning
confidence: 99%